Improving dietary quality and livelihoods using farm and wild biodiversity through an integrated community based approach in Busia and Turkana County, Kenya - Jordan, Irmgard; Oduor, Francis; Induli, Irene; Termote, Céline (2023)
Background: Food environment is an element of food systems which describes the context in which people select , acquire, prepare and consume food . Food environment determines thus diet quality and nutritional outcomes.